Carte des déclinaisons et inclinaisons de l'aiguille aimantée rédigée d'apr es la table des observations magnétiques faites par les voyageurs depuis l'année 1775. - La Pérouse, Jean-François de Galaup, comte de, 1741-1788 (1788)
Includes note. Sheet no. 8 consists of 2 hemispheres each in 46 cm in diameter. No. 1. [Europe, northwestern Africa, Newfoundland, Labrador, and northeastern South America] -- No. 2. [Southwestern coast of Africa and eastern coast of South America] -- No. 3. [Coasts of Indian Ocean from Cape of Good Hope to China] -- No. 4. [Coasts of Pacific Ocean from Philippines to Bering Sea] -- No. 5. [North America] -- No. 6. [Australia, New Zealand, and New Guinea] -- No. 7. [Pacific Ocean showing western coast of South America and Society Islands] -- No. 8. [Northern hemisphere and southern hemisphere]. Color;